P.2.11 Vitamin D deficiency and hepatitis B virus infection and risk of hematological malignancies among korean semiconductor workers: a case-control study. (April 2019) - Lee, Seokwon; Yang, Sarah; Koh, Jaewoo; Kim, Soo-Geun; Lee, Kyoungho
Abstract : Objectives: This study aims to identify an association between potential risk factors and risk of hematological malignancies, especially for Non-Hodgkin's Lymphoma (NHL) and leukemia, among Korean semiconductor workers. Methods: We collected 54 cases who ever worked over 30 days at a Korean semiconductor manufacturing company and were diagnosed as NHL (ICD-10 codes: C82–C85) and leukemia (C91–C95) from January 1 st 1998 to December 31 st 2017. A total of 324 controls, frequency matched by age and sex (1:6 ratios) with no diagnosis of hematological malignancies, were randomly selected. The information on work history, occupational exposure and medical examination data was also collected for the study analysis. Multivariable logistic regression analyses were performed to estimate odds ratios (ORs) after adjusting age, sex, education, employment year, smoking, alcohol and body mass index. Results: No significant association between hematological malignancies and occupational risk factors, including job title, cleanroom work and occupational exposures, was observed. As for leukemia, however, ORs were significantly increased by natural immunity to hepatitis B virus (HBV) [HBsAg(-), HBsAb(+), HBcAb(+)] (OR=11.92, 95% confidential interval 1.05–135.89) and a past or current (ever) HBV infection [HBsAg(+/-), HBsAb(+/-), HBcAb(+)] (6.52, 1.51–28.10). Furthermore, ORs for NHL were also significantly increased by insufficient serum 25-hydroxyvitamin D [25(OH)D] (12–20 ng/mL) (10.67, 1.27–89.53) and deficient 25(OH)D levels (<12 ng/mL) (12.22, 1.37–109.16) (p<0.05). Conclusions: Risk of hematological malignancies was not associated with occupational risk factors but significantly elevated by two factors, such as HBV infection and insufficient or deficient 25(OH)D level. A longitudinal cohort study is needed to confirm the association between these risk factors and cancers.